Billy Miller makes a wish - Henkes, Kevin; Henkes, Kevin (New York : Greenwillow Books, an imprint of HarperCollins Publishers, 2021)
"On his eighth birthday, Billy Miller wishes for something exciting to happen. None of his wishes are answered the way he expects, but he does have lots of surprises--and the final one is possibly the best one ever"--Provided by publisher.
Companion to: The year of Billy Miller.
3-6
Keywords: Wishes -- Juvenile fiction; Birthdays -- Juvenile fiction; Surprise -- Juvenile fiction; Families -- Wisconsin -- Juvenile fiction; Humorous stories; Wishes -- Fiction; Birthdays -- Fiction; Surprise -- Fiction; Family life -- Wisconsin -- Fiction; Humorous stories; Wisconsin -- Juvenile fiction; Wisconsin -- Fiction